2013
DOI: 10.1179/2045772312y.0000000028
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of curcumin on spinal cord in rabbit model with ischemia/reperfusion

Abstract: Background: Ischemic/reperfusion (I/R) injury of the spinal cord is a serious complication that can result from thoracoabdominal aortic surgery. Objective: To investigate the neuroprotective effect of curcumin against I/R injury in a rabbit model. Methods: A total of 36 rabbits were randomly divided into three groups: sham, I/R, and curcumin-treated group. Rabbits were subject to 30-min aortic occlusion to induce transient spinal cord ischemia. Neurological function was observed after reperfusion and spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Curcumin decreased oxidative stress by activating the Keap1/Nrf2/ARE signaling in diabetic rats [221]. Two other studies confirmed that curcumin decreased MDA levels and increased SOD and GPx levels after spinal cord ischemia-reperfusion injury [222,223]. Curcumin (300 mg/kg, i.p.)…”
Section: Caffeic Acid Phenethylmentioning
confidence: 90%
“…Curcumin decreased oxidative stress by activating the Keap1/Nrf2/ARE signaling in diabetic rats [221]. Two other studies confirmed that curcumin decreased MDA levels and increased SOD and GPx levels after spinal cord ischemia-reperfusion injury [222,223]. Curcumin (300 mg/kg, i.p.)…”
Section: Caffeic Acid Phenethylmentioning
confidence: 90%
“…Another report examined antioxidant effects of curcumin specifically in the reperfusion phase of ischemic SCI [ 28 ]. Though ischemia is a relatively uncommon etiology of SCI, inflammation-induced neurological damage remains a central aspect of pathogenesis in both traumatic and nontraumatic SCI.…”
Section: Antioxidant Effectsmentioning
confidence: 99%
“…According to our results, the persistent exposure to O 3 could possibly require a dynamic adjustment of the initial dose of CUR and thus, improve the efficiency of the neuroprotective effect. The antiapoptotic mechanisms of CUR are the reduction of cytochrome C translocation, the decrease in Bax expression, the increase in Bcl-2 level, and the inhibition of caspases 3 and 9 activity [62,63,64,65]. In addition, the preventive approach presented a more pronounced antiapoptotic effect, possibly due to an anticipated increase in Bcl-2 levels and through the enhanced activity of major antioxidant enzymes like superoxide dismutase, catalase, glutathione reductase, and glutathione peroxidase through the activation of Nrf2 by CUR [66].…”
Section: Discussionmentioning
confidence: 99%